2011
DOI: 10.1038/leu.2011.133
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 and IDH2 mutations in pediatric acute leukemia

Abstract: To investigate the frequency of isocitrate dehydrogenase 1 (IDH1) and 2 (IDH2) mutations in pediatric acute myeloid leukemia (AML) and acute lymphoid leukemia (ALL), we sequenced these genes in diagnostic samples from 515 patients (227 AMLs and 288 ALLs). Somatic IDH1/IDH2 mutations were rare in ALL (N=1), but were more common in AML, occurring in 3.5% (IDH1 N=3 and IDH2 N=5), with the frequency higher in AMLs with a normal karyotype (9.8%). The identified IDH1 mutations occurred in codon 132 resulting in repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 34 publications
7
76
3
1
Order By: Relevance
“…Subsequently, the mutation was also detected in myeloproliferative neoplasm (Pardanani et al, 2010;Tefferi et al, 2010), myelodysplastic syndrome (Kosmider et al, 2010), and non-Hodgkin lymphoma (Zou et al, 2010). Only three IDH-mutated cases were so far identified in ALL (Kang et al, 2009;Abbas et al, 2010;Andersson et al, 2011). Our observation confirmed the occurrence of IDH1 mutation in ALL.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Subsequently, the mutation was also detected in myeloproliferative neoplasm (Pardanani et al, 2010;Tefferi et al, 2010), myelodysplastic syndrome (Kosmider et al, 2010), and non-Hodgkin lymphoma (Zou et al, 2010). Only three IDH-mutated cases were so far identified in ALL (Kang et al, 2009;Abbas et al, 2010;Andersson et al, 2011). Our observation confirmed the occurrence of IDH1 mutation in ALL.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, the pediatric IDH1-mutated case reported by Andersson et al (2011) also had a normal karyotype and aberrant myeloid antigen expression of CD13 and CD33. The expression of the myeloid antigens in the IDH1 mutation carriers suggested that the leukemia clone of IDH1-mutated ALL may come from an early stage of hematopoiesis and IDH1 mutation may be involved in myeloid differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest in IDH biochemistry increased when mutations in one of the two homodimeric IDHs were associated with several subtypes of cancer, including gliomas and leukemias (13)(14)(15)(16). The IDH forward reaction, isocitrate decarboxylation, is inactivated by the common cancer-associated mutations that occur at Arg-132 of IDH1 or the analogous Arg-172 of IDH2 (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%